Penjajagan Awal Penerapan 'New Public Management' dalam Administrasi Kabupaten - Samodra Wibawa (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2002)
The popularity of New Public Management in the developed countries raises a question whether such a concept applicable in the Third World context. Relies on three focuses group discussion involving local bureaucrats, this article shows the desirability of New Public Management as model of local public administration, despite a strong awareness of the challenge they have to encounter.